200 Minus 1 - Räume im Shakespeare-Haus. - Humeltenberg, Hanna; Syring, Marie Luise; Gerlach, Peter; Smolik, Noemi (Köln : Shakespeare-Haus, 1988)
Jetelova, Magdalena ; Bijl, Guillaume ; Yilmaz, Adem ; Eckrich, Martin ; Blume, Bernhard Johannes ; Herold, Georg ; Lambertin, Theo ; Sery, Christian ; Luy, Wolfgang ; Polke, Sigmar ; Geismar, Jarg ; Mönnig, Peter ; Buthe, Michael ; Makowsi, Marina ; Enneper, Mic
200 Minus 1 - Räume im Shakespeare-Haus, Köln, Ausstellungsdauer vom 15.10. - 16.11.1988
boek